An epidemiological profile of crossfit participants in Portugal - Soares, Miguel Ribeiro Anes dos Ramos (2019)
Objective: CrossFit is a conditioning training program that has been rising worldwide, throughout the recent years. Despite CrossFit-based workouts having demonstrated considerable fitness gains, limited evidence is available concerning the injury incidence of CrossFit practice. The aim of this review was to characterize the epidemiological profile of CrossFit participants and to identify the rate of injury and the most commonly injured body parts among these athletes. Methods: Electronic databases were consulted (PubMed, PEDro, Medline, Proquest and Science Direct) and the following search terms were chosen to identify the published articles: “CrossFit epidemiology”, “CrossFit injury” and “CrossFit injuries”. Inclusion criteria included full-text articles published in English, regarding the injury incidence/rate and injured body parts of recreative or professional CrossFit participants. Articles published in the last ten years (2008-2017) were selected. Results: 8 articles were included in this review. The main findings indicate that the injury rate of CrossFit ranges from 1.94 to 3.1 injuries per 1000 training hours and that the most commonly injured body parts in CrossFit are the shoulder and the spine/lower back. Conclusion: CrossFit is comparable to other forms of sports or physical activities, regarding injury rates. Some strategies could be adopted in order to reduce the occurrence of injuries, such as the supervison of a qualified CrossFit coach. More scientific research is needed to validate the results showed in these reviewed articles.